The Sound of Horror - Silence & Sound Contrasts in Sci-Fi Horror Movies - Grøn, Nis (Tidsskrift for Medier, Erkendelse og Formidling, 2013)
The sound design of sci-fi horror movies plays a central role in creating the chilling pleasures produced by scary encounters with alien beings. Using Alien (1979) as a central example, this paper explores the idea that a specific stylistic element of the audiovisual design, designated as the (preliminary) shock point, constitutes a defining stylistic trait of the sci-fi horror genre’s spectacle. This article will seek to show that this stylistic element functions as a priming mechanism, playing with spectators’ expectations of the scary spectacle in sci-fi horror films as well as with their knowledge of the genre. Lyddesign i sci-fi-horrorfilm spiller en væsentlig rolle i skabelsen af de uhyggelige og ophidsende fornøjelser som opstår I mødet med skræmmende monstre. Med Alien (1979) som et centralt eksempel, undersøger denne artikel ideen om at et bestemt stilistisk element, betegnet chok punktet, udgør et afgørende stilistisk træk indenfor sci-fi-horror genren. Det er intentionen at vise at dette stilistiske element fungerer som en priming mekaniske, som både formår at påvirke tilskuerens forventninger til det fatale mødet med den/det fremmede og desuden leger med tilskuerens forudgående kendskab til genren og dens konventioner.Keywords: Sci-fi Horror, Alien, Sound Contrasts, Priming, Shock Points.